Theory of Vibro-Impact Systems and Applications - Babitsky, V. I. (Springer Berlin Heidelberg, 1998)
- Models of vibro-impact systems are widely used in machine dynamics, vibration engineering, and structural mechanics. - Only monograph on this subject in English language. - Systematically presents the theory of vibro-impact systems by analysis of typical engineering applications. - Experimental data and computer simulations are presented. - Targeted to engineers and researchers in design and investigation of mechanical systems as well as to lecturers and advanced students. Contents: - Vibro-impact systems. - Equivalent linearisation of vibro-impact systems.- Vibro-impact processes in systems with single degree of freedom. - Vibro-impact processes with multiple degrees of freedom. - Structural synthesis of self-sustaining vibro-impact systems
Keywords: Engineering; Vibration, Dynamical Systems, Control; Continuum Mechanics and Mechanics of Materials; Computational Intelligence; Mechanics; Statistical Physics, Dynamical Systems and Complexity; Statistical physics; Dynamical systems; Computational intelligence; Continuum mechanics; Vibration; Dynamics